Planning for Polycentricity in European Metropolitan Areas - expectations, rationales and practices - Peter Schmitt (European Regional Science Association (ERSA), 2010)
Polycentricity is one of the key words coined by the ESDP in 1999 to frame strategic planning at the transnational level. In recent years, however, the concept of polycentricity (and its inherent expectations) has increasingly trickled down as well to the regional level. The paper stems from observations and findings gained from assisting, advising and moderating an international expert group that consists of planners coming from a dozen of European metropolitan areas. Within this group the objective has been to identify major challenges, to reflect current methods, routines and debates and to share lessons and experiences with regard to the applicability and implementation of the concept of polycentricty in their respective metropolitan area. Using text analysis as well as participating observation, the paper will derive a typology of different analytical and normative understandings of polycentricity at the regional level. By exploring three thematic strands that have been chosen by the group to further discuss the potential performance of the concept of polycentricity (here: a: metropolitan governance and the implementation of plans and policies, b: urban sprawl and climate change response, c: functional labour division between centres and economic competitiveness/resilience), the paper will reflect similarities and differences of the planners' rationales and expectations, their current practices and activities and their experiences (so far) that are closely connected to the application of polycentricity within European metropolitan areas. The paper will also illustrate the high degree of context sensitivity to which the concept of polycentricity has to respond to in each of the twelve metropolitan areas that have been examined.
Keywords: 330